Analysis of the Financial Performance of State-Owned Enterprises (SOEs) in the Mining Sector Listed on the Indonesia Stock Exchange in 2018-2022 - Riko Mersandro Permana (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This study aims to analyze the financial performance of mining companies owned by the State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange. The objects taken in this study are mining companies listed on the Indonesia Stock Exchange in 2018-2022, with company codes PTBA, ANTM, and TINS. Analysis of corporate financial performance based on liquidity, activity, solvency ratio, profitability ratio, and DuPont analysis shows increases and decreases in value, but none are consistent. The results of the performance analysis of the three companies are expected to provide an overview to the management of the company concerned to develop future performance improvement strategies, as well as to investors as a basis for comparison, projections, and decision-making in investing in companies in the mining sector, especially mining companies owned by SOEs